ALTERATIONS IN SOIL PROPERTIES INDUCED BY PASSIVE RESTORATION BY Clidemia urceolata DC IN THE ATLANTIC RAINFOREST OF BRAZIL - Mateus, Felipe Araujo; Valcarcel, Ricardo; Bueno, Mateus Marques; da Mota, Kenedy Donizete Ribeiro (Floresta, 2018)
The passive restoration induced by nuclei of Clidemia urceolata affects the successional dynamics of ecosystems, and these in turn influence the physical and chemical characteristics of soils depleted by disturbed pastures, creating a positive synergy between the soil and the vegetation. This study evaluated the physical and chemical properties of the top 30 cm of the soil. This was carried out at the Federal Institute of Rio de Janeiro (IFRJ), Pinheiral Center, in the municipality of Pinheiral, state of Rio de Janeiro, Brazil, at five sampling sites with similar soil and physical environments. All the sites were pastures abandoned for different periods: 3 years of passive restoration (Site 1), 8 years (i.e., in an initial stage of colonization by plants; Site 2), 14 years (i.e., in an intermediate stage of colonization by plants; Site 3), 19 years (i.e., in an advanced stage of colonization by plants; Site 4), and 34 years (i.e., covered by fragments of secondary forest; Site 5). The following parameters were measured in the center of each site: a) mechanical resistance of the soil to penetration, b) apparent density, c) total porosity, d) macroporosity, e) microporosity, f) hydraulic conductivity, and g) nutrient content. The greatest contrasts in soil data were registered between 0 and 10 cm of depth, demonstrating the soil restoration done by the vegetation during passive restoration over 34 years. The development of Clidemia urceolata after 14 years is a key determinant of soil recovery, which modified its physical and chemical properties and created conditions for the environment to permit the growth and development of tree species, and the formation of forest fragments in less than 34 years of passive restoration, with no need of any additional efforts for the restoration of the disturbed areas.